Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1748-717x-6-141
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity after radiochemotherapy for glioblastoma using temozolomide - a retrospective evaluation

Abstract: PurposeRetrospective evaluation of toxicity and results after radiochemotherapy for glioblastoma.Methods46 patients with histopathologically proven glioblastoma received simultaneous radiochemotherapy (RCT). The mean age at the beginning of therapy was 59 years, the mean Karnofsky performance index 80%. 44 patients had been operated on before radiotherapy, two had not. A total dose of 60 Gy was applied in daily single fractions of 2.0 Gy within six weeks, 75 mg/m2/day Temozolomide were given orally during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 23 publications
1
33
1
1
Order By: Relevance
“…Hematologic toxicity related to concurrent and adjuvant temozolomide was emphasized in the EORTC/NCIC trial [2], with rates of severe thrombocytopenia and neutropenia of 7 %, similar to our study. Most reports on treatment tolerance among glioblastoma patients have included only the elderly [11][12][13]22] or focused on hematologic toxicity [14,23,24], with minimal data on morbidity leading to hospitalization. A recent population-wide study of glioblastoma patients reported readmission diagnoses 30 days after surgery, but included only elderly patients (age C 66) predominantly in the pretemozolomide era, and did not capture toxicities during CRT [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematologic toxicity related to concurrent and adjuvant temozolomide was emphasized in the EORTC/NCIC trial [2], with rates of severe thrombocytopenia and neutropenia of 7 %, similar to our study. Most reports on treatment tolerance among glioblastoma patients have included only the elderly [11][12][13]22] or focused on hematologic toxicity [14,23,24], with minimal data on morbidity leading to hospitalization. A recent population-wide study of glioblastoma patients reported readmission diagnoses 30 days after surgery, but included only elderly patients (age C 66) predominantly in the pretemozolomide era, and did not capture toxicities during CRT [22].…”
Section: Discussionmentioning
confidence: 99%
“…Disease-and treatment-related morbidity leading to hospitalization is particularly relevant [5,6], given that inpatient admission is associated with reduced quality of life among patients with incurable cancer including glioblastoma [7,8], as well as growing calls to reduce readmissions from quality-of-care and costcontainment perspectives [9,10]. Prior studies have reported on treatment tolerance specifically in the elderly glioblastoma population [11][12][13][14], and randomized trials have profiled adverse events among patients eligible for clinical trial inclusion [2]. However, little is known about the general glioblastoma population with regard to specific toxicities experienced by patients over the course of their disease, as well as the incidence, predictors, or reasons for hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…The patients receiving only adjuvant treatment seemed to fare no worse than those in the concomitant treatment group. This could probably be explained by the lesser toxicity of the former during initial treatment 51,52…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a 28% rate of grade 3–4 hematologic toxicity 26. A German study of 46 GBM patients with mean age 59 years who received concurrent chemoradiation highlights that hematologic toxicity may be persistent, with the mean duration of thrombocytopenia in that series being just over 2 months 27. Another Italian report on 58 GBM patients aged 65 years or older receiving concurrent and adjuvant TMZ reported a 25% rate of grade 3–4 mental status toxicity during the adjuvant TMZ phase, at a median time of approximately 6 months after completion of chemoradiation, although it is not clear whether this was attributable to combined RT/TMZ treatment as opposed to underlying disease progression 28.…”
Section: Standard Gbm Treatment: Applicable To the Elderly?mentioning
confidence: 99%